Synthesis of Acid Anhydrides via the Thermal or Photochemical Catalytic Hydrocarbonylation of Alkenes - Alexander M. Veatch (20629299) (2025)
The synthesis of symmetric aliphatic anhydrides with alkyl chains longer than C3 is typically accomplished by using traditional coupling methods, which often involve expensive and hazardous dehydrating agents with poor atom economy. A catalytic method for producing high-nuclearity (C3+) aliphatic anhydrides from common alkenes, carboxylic acids, and carbon monoxide gas using low loadings of a palladium catalyst system is reported here. Benzoyl chloride proved to be essential for avoiding the formation of Pd black and preserving high catalyst activity. Mechanistic studies of cationic and neutral acyl chloride complexes emphasize the crucial role of benzoyl chloride in maintaining the catalytic performance. A complementary catalytic method using visible light irradiation produces anhydrides at lower pressures of CO and with improved regioselectivities relative to those of the thermal reaction.